Maximizing sales: synergy of job autonomy, innovation culture, emotional intelligence, and a touch of creativity - Muhtarom, Abid; Ausat, Abu Muna Almaududi; Azzaakiyyah, Hizbul Khootimah; Syamsuri, Syamsuri; Suherlan, Suherlan (LPPM ISNJ Bengkalis, 2025)
Purpose – This study examines the impact of job autonomy, innovation culture, and emotional intelligence on the sales performance of MSMEs, with creativity as a mediating variable. Given the intense competition in the business environment, MSMEs must foster innovation and creativity to enhance their sales performance. Job autonomy enables MSME owners and managers to make independent decisions, fostering creativity in problem-solving. At the same time, an innovation culture promotes boldness in generating new ideas, and emotional intelligence strengthens customer and team relationships. Method – This research adopts a quantitative approach using the SEM-PLS methodology, with a sample of 100 MSMEs in Bandung city, Indonesia, selected through purposive sampling. Data was collected via an online questionnaire. Findings – The findings reveal that job autonomy, innovation culture, and emotional intelligence significantly and positively affect sales performance, with creativity playing a crucial mediating role. Implications – Theoretically, this study extends the self-determination theory (SDT), organizational innovation theory, and resource-based view (RBV) theory by demonstrating the interplay between autonomy, innovation, and emotional intelligence in enhancing creativity and sales performance. Practically, the findings highlight the need for MSME owners to foster workplace autonomy, encourage an innovative work culture, and enhance employees' emotional intelligence to improve business success through creative approaches.